2022
DOI: 10.3390/ani12213008
|View full text |Cite
|
Sign up to set email alerts
|

Stress Assessment of Wild Boar (Sus scrofa) in Corral-Style Traps Using Serum Cortisol Levels

Abstract: Capture of wild boar in corral-style traps with subsequent culling is increasingly used for population management. The method is debated due to animal welfare concerns making welfare studies in traps necessary. While previous studies focused on behaviour and injuries, this study dealt with the physiological aspect. Cortisol levels in wild boar caught in corral-style traps (50–90 qm2, n = 138) were compared with those killed during single (n = 37) and driven hunts (n = 90). Collected sera were purified by solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Since escape behavior can lead to injuries, trapping entire sounders is preferable from an animal welfare perspective. These results are in line with previous studies in which the capture of single individuals is associated with higher cortisol levels and increased escape behaviors than wild boar captured in a larger group [14,24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Since escape behavior can lead to injuries, trapping entire sounders is preferable from an animal welfare perspective. These results are in line with previous studies in which the capture of single individuals is associated with higher cortisol levels and increased escape behaviors than wild boar captured in a larger group [14,24].…”
Section: Discussionsupporting
confidence: 93%
“…Individually trapped wild boar exhibited more escape behavior and more escape attempts in the presence of humans than at the beginning of trap closure [ 14 ]. Westhoff et al [ 24 ] confirmed this using cortisol levels, showing that wild boars captured in groups had lower cortisol levels than those captured individually. In addition, cortisol levels were higher in wild boar corral-style traps compared to other hunting methods [ 24 ].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations